Folklore elements in Aleksey Begzin-ool’s poetry - Oorzhak, Lidya H. (The New Research of Tuva, 2013)
Article analyzes the pieces of poetry by A.Begzin-ool, a well-known writer in Tuva. His works have a distinguished national philosophy, wisdom, kind irony, not persistence, delicate ability to give advice without edification. Author himself is a great expert in folk language, habits and traditions.